2017
DOI: 10.3390/rs9060578
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Aerosol Optical Depth Using the Empirical Orthogonal Functions (EOFs) Based on PARASOL Multi-Angle Intensity Data

Abstract: Aerosol optical depth (AOD) is a widely used aerosol optical parameter in atmospheric physics. To obtain this parameter precisely, many institutions plan to launch satellites with multi-angle measurement sensors, but one important step in aerosol retrieval, the estimation of surface reflectance, is still a pressing issue. This paper presents an AOD retrieval method based on the multi-angle intensity data from the Polarization and Anisotropy of Reflectances for Atmospheric Science coupled with Observations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…In general, the correlation is highest for Warsaw (r 2 of 0.91) despite a large difference of the measured wavelength. It is also high for Raciborz (0.84) and for Rzecin (0.8), which is in agreement with correlations reported in literature [30]. For Warsaw and Raciborz clear separation of the data points is visible; however, different trends are discerned.…”
Section: Satellite-derived Aerosol Optical Depth Maps Of Polandsupporting
confidence: 81%
See 2 more Smart Citations
“…In general, the correlation is highest for Warsaw (r 2 of 0.91) despite a large difference of the measured wavelength. It is also high for Raciborz (0.84) and for Rzecin (0.8), which is in agreement with correlations reported in literature [30]. For Warsaw and Raciborz clear separation of the data points is visible; however, different trends are discerned.…”
Section: Satellite-derived Aerosol Optical Depth Maps Of Polandsupporting
confidence: 81%
“…The SEVIRI collects data in 12 spectral channels (in a range of 635 nm to 13.4 µm) with spatial resolution for a sub-satellite point of 3 km for channels 1-11 and 1 km in channel 12 (High Resolution Visible channel). Several approaches to the SEVIRI AOD daytime and night-time retrieval have been reported (e.g., [28][29][30]). In this paper we use the prototype version of the SEVIRI AOD algorithm developed in-house [28] that has been modified to provide AOD retrieval in near real-time over the territory of Poland.…”
Section: Retrieval Of Seviri Aerosol Optical Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration and cloud‐screening procedures are also consistent between SONET and AERONET, and thus, the data quality and aerosol product accuracy are comparable as suggested by data analyses (Li et al, ) of joint campaigns (Holben et al, ). The SONET data set has been employed in many applications, including validation of satellite products (e.g., Zhang, Li, Qie, et al, ), assimilation into chemical transport models (e.g., Chang et al, ), and radiative forcing studies (e.g., Li et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Guo et al [33] revealed the spatial and temporal characteristics of AOD values during 1980-2008 over mainland China using the TOMS AOD and MODIS AOD products (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). Meanwhile, many studies on the spatial and temporal variations of AOD values in regional scale in Chinawere conducted using meteorological measurement and satellite signals [10,26,[34][35][36][37][38][39][40]. However, few studies have been made for analyzing the characteristics and driving factors of AOD values in different climate zones and terrain features over mainland China, due to the relative sparse AOD and meteorological measurements.…”
Section: Introductionmentioning
confidence: 99%